Determinants of pertussis among young children in Selangor, Malaysia - Juliana Mansor; Halim Ismail; Noriah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
The resurgence of pertussis infection worldwide, including Malaysia, is alarming. Young children have the highest reported pertussis incidence and death rates. However, little is known of the risk factors of pertussis in Malaysia. In this study, we aimed to determine the risk factors of pertussis infection among children. We conducted a case-control study involving 143 children aged ≤2 years from Selangor, Malaysia. The children were identified from eNotifikasi, a web-based notification site, from 1 January to 31 December, 2018. Information on clinical presentation and risk factors were collected during investigation of the case by the district health office. Multivariate analysis showed that the odds for pertussis were higher among children aged <3 months (adjusted odds ratio (aOR) 5.54; 95% confidence interval (CI); 1.835, 16.710) and among children who had not received their vaccination according to age (aOR 5.641; 95% CI; 1.845, 17.245). The mean duration of cough among the cases was 10.22 days (SD 8.964); that of the controls was 6.47 days (SD 7.098). Paroxysmal cough (93.6%) was the predominant symptom among the cases. A total of 42.6% of cases were aged <2 months, whilst most of the controls were aged >5 months (40.4%). Up to 42.6% of cases and 68.7% of controls were immunised according to their age. Therefore, it is important to ensure that children are vaccinated once they have attained the appropriate age.